Good practices for interacting with users of meteorological, climate and environmental services - D'Amen, Daniela (2024)
Fil: D´Amen, Daniela. Servicio Meteorológico Nacional. Dirección Nacional de Pronósticos y Servicios para la Sociedad; Argentina